Growth, Pigment and Protein Production of Spirulina platensis under different Ca(NO3)2 concentrations - Muhammad Fakhri; Prive Widya Antika; Arning Wilujeng Ekawati; Nasrullah Bai Arifin (Department of Aquaculture, 2020)
Spirulina platensis is a filamentous cyanobacterium that has been commerically used for fish feed and human food supplement. Low-cost production of Spirulina is needed when considering large-scale culture especially for industrial purposes. The aim of this study was to explain the effect of calcium nitrate (Ca(NO3)2) on growth, biomass, pigment, and protein production of S. platensis and to determine the best calcium nitrate concentration for Spirulina production.The microalgae was cultured at four calcium nitrate concentrations (1, 1.5, 2.0 and 2.5 g/L) with salinity of 15 ppt, constant light intensity of 4,000 lux and photoperiod of 24:0 light:dark cycles for 4 days. The results showed that different calcium nitrate concentrations remarkably affected the growth, biomass production, pigment and protein content of S. platensis (p<0.05). The highest specific growth rate of 0.721 day-1 and biomass concentration of 1.512 g/Lwere achieved at calcium nitrate concentration of 2.5 g/L. Moreover, the algae had the highest chlorophyll-a, carotenoid and protein content at 2.5 g L-1. Increasing calcium nitrate concentration from 1 to 2.5 g/L led to an increase in biomass, pigment and protein production of S. platensis. However, there was no significant difference between 2 and 2.5 g L-1 calcium nitrate concentrations. We suggest that 2-2.5 g/L Ca(NO3)2 concentration can be used profitably for S. platensis production.